Wood Chippers: Influence of Feed Channel Geometry on Possibility of Musculoskeletal System Overload - Bartosz, Wieczorek; Giredrowicz, Marcin; Kukla, Mateusz; Nati, Carla; Warguła, Łukasz (Croatian Journal of Forest Engineering, 2025)
The position and shape of the feed channel (FC) in low-power woodchippers significantly affect the way machine operators' upper limbs move. The execution of operator's movements can be accomplished in different working areas: comfortable, acceptable, or not recommended due to overloads in the musculoskeletal system. Three groups of male subjects from Central Europe, divided according to anthropometric dimensions from centile groups C5, C50 and C95, were selected to assess upper limb movement, by adopting a Motion Capture measurement method. The tests have shown that the limb closer to the FC (left hand in this study) carries out all the movements in the allowed zone (AZ), while between 79% and 96% of the limb movement is contained within the comfort zone (CZ). The right limb has a greater amplitude of motion outside the CZ working area – from 0% to 69% and for AZ – in the CZ can vary by up to 51%. It was found that commercial low-power woodchippers deployed in urban areas, typically induce overloads in the musculoskeletal system of the operator during the use. Based on the research results, the authors see the need to improve FC position adjustment for the operators of these machines.